Cochlear dysfunction as an early biomarker of cognitive decline in normal hearing and mild hearing loss - Vicente Medel; Paul H. Delano; Chama Belkhiria; Alexis Leiva; Cristina De Gatica; Victor Vidal; Carlos F. Navarro; Simon San Martín; Melissa Martínez; Christine Gierke; Ximena García; Mauricio Cerda; et al. (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2024)
Abstract INTRODUCTION Age‐related hearing loss is an important risk factor for cognitive decline. However, audiogram thresholds are not good estimators of dementia risk in subjects with normal hearing or mild hearing loss. Here we propose to use distortion product otoacoustic emissions (DPOAEs) as an objective and sensitive tool to estimate the risk of cognitive decline in older adults with normal hearing or mild hearing loss. METHODS We assessed neuropsychological, brain magnetic resonance imaging, and auditory analyses on 94 subjects > 64 years of age. RESULTS We found that cochlear dysfunction, measured by DPOAEs—and not by conventional audiometry—was associated with Clinical Dementia Rating Sum of Boxes (CDR‐SoB) classification and brain atrophy in the group with mild hearing loss (25 to 40 dB) and normal hearing (<25 dB). DISCUSSION Our findings suggest that DPOAEs may be a non‐invasive tool for detecting neurodegeneration and cognitive decline in the older adults, potentially allowing for early intervention.